2019
DOI: 10.7454/proust.v2i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Development of Community-Based Mental Health Interventions in The Philippines: An Ecological Perspective

Abstract: Although urbanization is linked to modernization and economic growth, it is also associated with overcrowding, population density, poverty, inadequate social services, and violence, all of which put the urban poor at risk of environmental health problems and other dangers. Moreover, experiences of environmental and psychological adversity increase vulnerability to mental health disorders. Unfortunately, in low resource countries, mental health treatment is largely inaccessible to the poor. This paper describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Stigma was also reported as deterrents to both PWUDs and stakeholders. These findings reinforce results of a previous study in the Philippines that the stigma is exacerbated by statements of government leaders that addicts are not human (Viray, 2017) and peste (pest) with extra-judicial killings referred to as a form of pest control (Hechanova, 2019). The results reinforce the need to address stigma and to provide better understanding of drug use and treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Stigma was also reported as deterrents to both PWUDs and stakeholders. These findings reinforce results of a previous study in the Philippines that the stigma is exacerbated by statements of government leaders that addicts are not human (Viray, 2017) and peste (pest) with extra-judicial killings referred to as a form of pest control (Hechanova, 2019). The results reinforce the need to address stigma and to provide better understanding of drug use and treatment.…”
Section: Discussionsupporting
confidence: 89%
“…By 2018, drug arrests numbered 149,265, and 4,500 had been killed for drug involvement (Talabong, 2018). The punitive approach and messaging by government leaders that drug users are criminals and pests also exacerbated the stigma toward PWUDs (Hechanova, 2019). On the bright side, some LGUs adopted evidence-informed programs such as the Katatagan, Kalusugan, at Damayan ng Komunidad (translated as Resilience, Health and Care in the Community; KKDK), that utilized cognitive behavioral therapy, motivational interviewing, mindfulness, and family systems theory (Hechanova et al, 2019).…”
Section: Cbdr In the Philippinesmentioning
confidence: 99%
“…This is the finding of several resilience researchers. The research of Hechanova;s (2019) found that at the level of individual, spiritually occurs to be a factor of resiliency in both handling disasters and recuperate from using drugs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for disaster survivors, family and community members are crucial for both social and instrumental support. The group intervention format also helps the survivor to feel as if they were not alone (Hechanova, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, they have developed largely in response to the current political strategy and though financially supported by aid organizations, have the support of communities and many in congress, local government and law enforcement. Training and programme development have continued after a brief hiatus at the beginning of the pandemic [ 40 , 41 ].…”
Section: Country Case Examplesmentioning
confidence: 99%